A Survey on Cosmic Students Estimation Challenge - Hacaloğlu, Tuna; Say, Bilge; Demirörs, Onur; Ünlü, Hüseyin; Küçükateş Ömüral, Neslihan; Demirörs, Onur (CEUR-WS, 2022)
Software project management is a significant software engineering practice that is highly related to achieving software-specific project goals. This study aims to share students’ perceptions of incorporating an international software estimation challenge called “COSMIC Students’ Estimation Challenge” into a software project management course. For this aim, students were taught the COSMIC Functional Size Measurement method and entered the competition. After the competition, a questionnaire asking for the students’ opinions was collected. The objective of the research is to get an insight into to what extent incorporating this type of competition activity -a challenge- can contribute to students’ learning perceptions. In the long run, the findings can contribute to creating a foresight about making the necessary curriculum arrangements to form a more up-to-date and dynamic education plan by including the methods applied in the software industry in Software Engineering education. The results suggest that this kind of competition experience and preparation is helpful for students to learn the COSMIC method.
Keywords: COSMIC; Challenges; Gamification; Project management education